Analysis of the Values of Sultan Muhammad Al-Fatih's Da'wah in the Book by DR. Ali Muhammad Ash-Shallabi - Agus Saifuddin Amin; M. Khairun Azmi (al-Afkar, Journal For Islamic Studies, 2024)
Dakwah has another meaning namely, religious broadcasting, calls to embrace, study and practice religious teachings. While the meaning of preaching is to invite or call for learning and practicing religious teachings. The main purpose of da'wah is to make people always follow His way so that happiness in this world and in the hereafter is blessed by Allah SWT. The da'wah values that we want to examine are from previous Islamic figures, one of whom is Sultan Muhammad Al-Fatih in a book by DR. Ali Muhammad Ash-Shallabi is known for his preaching methods which are synonymous with war, but if studied more deeply Al-Fatih also carried out various kinds of humanist preaching methods, full of wisdom (al-hikmah) which proved to be efficient in his time. In this study using the approach of Content Analysis, namely research that is in-depth discussion of the contents of a written or printed information in the mass media. This type of research is using qualitative research, namely to describe various situations in the form of phenomena, conditions, and situations that exist in the community which are the object of research. The data source here uses primary data obtained directly from the original source and secondary data obtained indirectly through intermediary media. The data collection technique used by the author in this study is the documentation technique. The data analysis used is Content Analysis, namely by analyzing a document in the form of written works, books, films, pictures, biographies, letters, newspapers, magazines, bulletins and others. From the results of this study, it is known that Sultan Muhammad Al-Fatih carried out da'wah activities namely, with worship activities towards schools and institutes, worship activities towards translation activities, worship activities towards government management and worship activities towards the army and navy. Then from the da'wah of social behavior, namely, social behavior towards scholars, social behavior towards poets and writers, social behavior towards prosperity, development and hospitals, social behavior towards trade and industry and social behavior towards justice.